Peran Guru sebagai Motivator Belajar dan Menanamkan Jiwa Nasionalisme Peserta Didik Sekolah Indonesia Kuala Lumpur (SIKL) - Muzakir, Muchammad Ibnu; Kholik, Mohammad Fariz Dzikrul; Yusra, Andi Nurfadilah; Salsabilah, Annisa Safitri; Habib, Hafiz Farhan (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to get an overview and examine learning motivation and instilling nationalist values in students at the Kuala Lumpur Indonesian School (SIKL). The approach used in this research is a qualitative approach with descriptive methods. In collecting data, researchers used several techniques, namely through interviews, observation and documentation studies. The data that was collected was analyzed descriptively qualitatively using the constant comparison method and the Constant Comparative Method. The research location is the Indonesian School Kuala Lumpur (SIKL) Kuala Lumpur, Malaysia. The research results show that: (1) The teacher's role is as a motivator and understands the steps that can be taken to achieve optimal learning conditions for students. (2) The role of teachers in teaching nationalist values in classroom learning. (3) The teacher's role is to foster students' love and enthusiasm for nationalist values. (4) The teacher facilitates students to preserve the Indonesian language. (5) The role of the teacher in developing students' nationalistic character and attitudes through the learning process in the classroom and outside the classroom is very important where a PPKN teacher will be able to carry out his obligations and responsibilities if the teacher has first mastered and is able to apply positive behavior to himself so that he can become a role model for his students